Comparative study on yield and yield attributes of hybrid, inbred, and NPT rice genotypes in a tropical irrigated ecosystem - Islam, M. Sirajul; Peng, Shaobing; Visperas, Romeo M.; Bhuiya, M. Sultan Uddin; Hossain, S.M. Altaf; Julfiquar, A.W. (Bangladesh Academy of Sciences, 1970)
Yield potential of 16 rice genotypes including 12 hybrids, 3 inbreds, and I new plant type (NPT), were studied at the International Rice Research Institute farm under optimum crop management to achieve maximum attainable yields during the wet season (WS) of 2004 and dry season (DS) of 2005. Yield and yield components were determined at maturity. 1R76712H produced the highest grain yield (7.7 t/ha) followed by 1R75217H and Magat (7.6 t/ha) in WS; in DS, 1R79118H produced the highest grain yield (9.17 t/ha) followed by 1R73855H (8.9 t/ha) and SL-8H (8.8 t/ha. The high yield of hybrid rice was due to high harvest index (0.50). Hybrid produced significantly higher productivity (80.2 kg/ha/day) than inbred in DS, but the difference was not significant in WS. Hybrid produced higher spikelets/panicle and 1000-grain weight than inbred rice. Spikelet filling percent was higher in inbred than hybrid rice. The NPT rice genotype had the lowest spikelet filling percent, but the highest 1000-grain weight across the season. Keywords: Yield; yield attributes; hybrid and inbred rice genotypes. DOI: 10.3329/bjar.v35i2.5897Bangladesh J. Agril. Res. 35(2) : 343-353, June 2010